Optimization of technological processes at the terminal - Bagdoniene, Danute; Mazūra, Skirmantas (Transport, 2004)
The reliability of terminal operation is analysed by statistical methods based on the collected statistical data. Major estimates are made on a specified credibility level (probability). When the terminal is highly reliable and the interaction between transport facilities, freight senders and recipients is efficient, the work with minimum reserves and lower storage costs may be planned. The optimization problem of managing the interaction of railway and road transport at the seaport terminals is considered and the number of transfers to the port or approach roads is determined. First Published Online: 27 Oct 2010